BRD4 inhibition and FXR activation, individually beneficial in cholestasis, are antagonistic in combination - Hyunkyung Jung; Jinjing Chen; Xiangming Hu; Hao Sun; Shwu-Yuan Wu; Cheng-Ming Chiang; Byron Kemper; Lin-Feng Chen; Jongsook Kim Kemper (JCI Insight, 2021)
Activation of farnesoid X receptor (FXR) by obeticholic acid (OCA) reduces hepatic inflammation and fibrosis in patients with primary biliary cholangitis (PBC), a life-threatening cholestatic liver failure. Inhibition of bromodomain-containing protein 4 (BRD4) also has antiinflammatory, antifibrotic effects in mice. We determined the role of BRD4 in FXR function in bile acid (BA) regulation and examined whether the known beneficial effects of OCA are enhanced by inhibiting BRD4 in cholestatic mice. Liver-specific downregulation of BRD4 disrupted BA homeostasis in mice, and FXR-mediated regulation of BA-related genes, including small heterodimer partner and cholesterol 7 alpha-hydroxylase, was BRD4 dependent. In cholestatic mice, JQ1 or OCA treatment ameliorated hepatotoxicity, inflammation, and fibrosis, but surprisingly, was antagonistic in combination. Mechanistically, OCA increased binding of FXR, and the corepressor silencing mediator of retinoid and thyroid hormone receptor (SMRT) decreased NF-κB binding at inflammatory genes and repressed the genes in a BRD4-dependent manner. In patients with PBC, hepatic expression of FXR and BRD4 was significantly reduced. In conclusion, BRD4 is a potentially novel cofactor of FXR for maintaining BA homeostasis and hepatoprotection. Although BRD4 promotes hepatic inflammation and fibrosis in cholestasis, paradoxically, BRD4 is required for the antiinflammatory, antifibrotic actions of OCA-activated FXR. Cotreatment with OCA and JQ1, individually beneficial, may be antagonistic in treatment of liver disease patients with inflammation and fibrosis complications.